The Importance of Enactive Processes Through Experiments in Improving Learning Outcomes Based on Bruner's Theory - Dzulkifli Nurul Huda; Dyah Ismi Safitri; Supeno Supeno; Singgih Bektiarso (Peneliti.net, 2026)
This study aims to determine the effect of applying the enactive process through experimental activities on student learning outcomes in science education. The enactive process, as proposed by Bruner, emphasizes the direct involvement of students in manipulating objects and conducting real experiences as the basis for concept formation. This study uses a literature review approach to examine scientific publications on the role of enactive processes through experimental activities in improving learning outcomes based on Bruner's theory. Data were obtained from reputable articles on Google Scholar and ScienceDirect that were relevant and up-to-date, then analyzed thematically to reveal the relationship between the enactive process, student engagement, and improved learning outcomes. The results of this study indicate that the enactive process plays an important role in science learning because it directly involves students through experiments, thereby increasing student activity, conceptual understanding, science process skills, and overall learning outcomes.